La valse des étiquettesQuelques problèmes posés par l’appréciation des films - Laurent Jullier (Mise au Point)
What kind of labels are “masterpiece” and “turkey” ? Do they refer to real qualities or do they only show the personal value one gives to a particular movie? If there was indipensable conditions for a film to be excellent or mediocre, at least, and if these conditions were lasting… but such certainties do not exist. The essay tries to face these difficulties using theoretical tools borrowed from the fields of philosophy (the idea of supervenient properties) and sociology (“situations” as described by E. Goffman). Finally the question of hierarchized appreciations is raised.